Identification of potential allergens in larva, pupa, moth, silk, slough and feces of domestic silkworm (Bombyx mori). (15th November 2021) - He, Weiyi; Li, Shuiming; He, Kan; Sun, Fan; Mu, Lixia; Li, Qingrong; Yi, Jiang; He, Zhendan; Liu, Zhigang; Wu, Xuli
Highlights: 34 new potential allergens in silkworm body (larvae, pupa and moths) are identified. 11 new potential allergens in metabolites (silk, slough and feces) are identified. Positive rate of IgE binding to allergens in silkworm body is higher than metabolite. Some potential allergens of silkworm share high homology with known allergens. Abstract: The silkworm ( Bombyx mori ) is an important economic insect that can be used as food in many countries in Asia. However, silkworms and their metabolites are an important source of allergens, which can induce severe allergic reactions. So far, there are no systematic studies on the potential allergens in silkworm and its metabolites. These studies have important guiding significance for the prevention, diagnosis, and treatment of silkworm allergy. The aim of this study was to identify the potential allergens from larva, pupa, moth, silk, slough and feces of silkworm and analyze the sequence homology of silkworm allergens with other allergens identified in the Allergenonline database. We have found 45 potential allergens in silkworm. The results of the homology comparison suggested that silkworm allergens likely cross-react with those of Dermatophagoides farinae, Aedes aegypti, Tyrophagus putrescentiae, Triticum aestivum and Malassezia furfur .